Screen printing on Cu2ZnSnSxSe1-x thin film for photovoltaic application - Kong, Ren Hwai (2014)
The main fabrication method of solar cell is done by vacuum deposition. Screen printing , a common T-shirt patterning process, can be used as direct liquid coating for thin film solar cell. Beside saving equipment cost for vacuum setup, screen printing has larger deposition area and is compatible with roll-to-roll process. [1st Award]